Shared risk factors for arterial cardiovascular diseases and venous thromboembolism - Småbrekke, Birgit (Journal of Thrombosis and Haemostasis, 2019)
Summary - Extensive evidence support an association between arterial cardiovascular disease (CVD, i.e. myocardial infarction [MI] and ischemic stroke), and subsequent venous thromboembolism (VTE, i.e. deep vein thrombosis [DVT]) and pulmonary emboli [PE]). However, the mechanism behind the associations remains unclear. The aim of this thesis was to investigate the impact of ischemic stroke on VTE and to investigate potential shared risk factors for arterial CVD and VTE. All papers in this thesis utilize data from the Tromsø Study. The study populations for Paper I, II and III were recruited from the fourth, fifth and sixth survey of the Tromsø study. In Paper IV, we recruited a subgroup participants with genetic information from the fourth survey of the Tromsø Study and from the second survey of the Nord-Trøndelag Health (HUNT) Study. Ischemic stroke was associated with a transient increased risk of VTE, and the risk was particularly high for provoked events. The association persisted after adjusting for potential confounders, indicating that the stroke itself increased the VTE risk. We found no association between formation, presence or progression of atherosclerosis and VTE in time-varying analyses, indicating that atherosclerosis does not represent the missing link for the association between arterial CVD and VTE. Except for body mass index, none of the traditional cardiovascular risk factors increased the risk of VTE, and risk estimates for MI and VTE based on a single baseline measurement and repeated measurements corresponded well. Lastly, we showed that the association between a family history of MI (FHMI) and VTE is not explained by prothrombotic genotypes. Our findings imply a strong and transient increased risk of VTE after ischemic stroke and that the association between arterial CVD and VTE cannot be explained by atherosclerosis. Of the well-known cardiovascular risk factors, only age, obesity and FHMI are associated with VTE. The association between arterial CVD and subsequent VTE is only partly ...